Targeting mTOR in Glioblastoma: Rationale and Preclinical/Clinical Evidence - Mecca, Carmen; Giambanco, Ileana; Donato, Rosario; Arcuri, Cataldo (Disease Markers, 2018)
The mechanistic target of rapamycin (mTOR) drives several physiologic and pathologic cellular processes and is frequently deregulated in different types of tumors, including glioblastoma (GBM). Despite recent advancements in understanding the molecular mechanisms involved in GBM biology, the survival rates of this tumor are still disappointing, primarily due to the lack of efficacious treatments. The phosphatase and tensin homolog (PTEN)/phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT)/mTOR pathway has emerged as a crucial player in GBM development and progression. However, to date, all the attempts to target this pathway with PI3K, AKT, or mTORC1 inhibitors failed to improve the outcome of patients with GBM. Despite these discouraging results, recent evidence pointed out that the blockade of mTORC2 might provide a useful therapeutic strategy for GBM, with the potential to overcome the limitations that mTORC1 inhibitors have shown so far. In this review, we analyzed the rationale of targeting mTOR in GBM and the available preclinical and clinical evidence supporting the choice of this therapeutic approach, highlighting the different roles of mTORC1 and mTORC2 in GBM biology.